Authoritative texts and reception history : aspects and approaches - Batovici, Dan, 1976- (Biblical Interpretation Series, 2017)
Reception history has emerged over the last decades as a rapidly growing domain of research, entertaining a notable methodological diversity. Authoritative Texts and Reception History samples that diversity, offering a collection of essay that discuss various reception-historical issues, from a plurality of perspectives, across several fields: Hebrew Bible/Old Testament, Pseudepigrapha and the Dead Sea Scrolls, New Testament, early and late-antique Christianity. While furthering specific discussions in their specific fields, the contributions included here-authored by both established and emerging scholars-illustrate just how wide the umbrella of 'reception history' can be, and the varied range of topics, concerns and approaches it can accommodate.